THE ROLE OF ACUTE INFLAMMATORY RESPONSE IN THE DEVELOPMENT OF ULCER BLEEDING - Sulaieva, O.N.; Deliy, V.Yu. (World of Medicine and Biology, 2015)
The goal of this study was to estimate the severity of the acute inflammatory response in patients with primary and recurrent bleeding under peptic ulcers of stomach and duodenum. Evaluation of peripheral blood and biopsies of the marginal zone of ulcers was conducted among patients with acute ulcer bleeding who were subdivided into two groups according the outcome: with effective hemostasis (group 1, n = 35) and in the development of rebleeding (group 2, n = 40). There were no differences between patients of the 1st and 2nd groups with respect to age, male sex, and previous ulcer disease. A comparison of peripheral blood reaction to acute ulcer bleeding did not demonstrate differences in terms of erythrocyte, platelet and hemoglobin concentrations, total white blood cell count. Despite the increase of neutrophil count in peripheral blood of bleeders comparing with control (P=0,031), there were not significant differences between 1st and 2nd groups. However, plasma fibrinogen concentration in rebleeders was significantly higher than in 1st group patients (P=0,01) A comparison of histological changes in the ulcer margin and intact mucosa has revealed that the development of bleeding is associated with ischemic injury and acute inflammatory reaction in the ulcer margin, regardless of the ulcer location. Compared with patients from the 1st group, rebleeders exhibited more severe neutrophilic infiltration that was associated with secondary damage and an expansion in width of the necrosis area that might be one of the reasons for rebleeding. However, there were no correlation between peripheral blood leukocytes or neutrophils and severity of local PMNs infiltration in ulcer margin. The morphometric analysis of immunohistochemical stains showed an increased representation of macrophages at the ulcer margin compared to the intact mucosa (P
Keywords: peptic ulcer; acute bleeding; inflammation; neutrophils; macrophages